Proses Penyelesaian Kenetu Bewoten Terhadap Pihak-Pihak Yang Bersengketa Menurut Adat Lamaholot Adonara Flores Timur - Rahmat Lebu Raya; Simplexius Asa; Kornelia Melansari Lewokeda (Artemis Law Journal, 2026)
Dispute resolution is not solely conducted through the state's formal legal channels, but is more often settled through customary mechanisms that prioritize family values and social balance. This study aims to understand and analyze the dispute resolution process according to Lamaholot customary law, the role of traditional leaders in resolving disputes, as well as the relevance and effectiveness of such customary law in the context of modern society. This research employs a qualitative method with a juridical-sociological approach. Data were obtained through literature review, in-depth interviews with traditional leaders and local community members, as well as direct observation of customary dispute resolution practices in accordance with Lamaholot traditions. The findings reveal that dispute resolution under Lamaholot customary law involves stages such as family deliberations, customary meetings, and ultimately, traditional peace rituals. The process is aimed at restoring social harmony and preserving the dignity of the disputing parties. It not only resolves the issues materially, but also addresses them morally and spiritually. The study concludes that Lamaholot customary law still holds strong normative authority and can coexist with the national legal system in resolving disputes. This customary law reflects local wisdom that must be preserved, maintained, and integrated into the development of an inclusive national legal system rooted in the cultural values of the community.